The disarticulation of regional integration in South America: some considerations on UNASUL - Ribeiro, Luís Henrique Matos (2024)
In the geopolitical context of Latin America, Brazil has played a very important role in regional integration with the formation of the economic bloc, the Southern Common Market (MERCOSUR), in 1991, and the intergovernmental bloc, the Union of South American Nations (UNASUR), in 2008. In the early 2000s, the integration process was strengthened with the arrival of left and center-left governments, facilitating dialogue in search of regional integration, already proposed from various attempts since 1960. However, with the arrival of right and far-right governments in the middle of the second decade of the 2000s, a disarticulation in regional integration begins, UNASUR, for example, was emptied, and governments with a right-wing bias created Prosul (Forum for the Progress of South America). This article aims to understand regional integration in South America from the 2000s, with the creation of UNASUR, highlighting its challenges, its disarticulation, and the attempt to resume today. For the elaboration of this article, the methodology was based on bibliographic research, in addition to the collection of secondary data on official websites for the realization of tables, maps, and graphics, necessary for the comprehension of the theme. UNASUR represented an important project of regional integration, with a bias not only economic, including multiple dimensions, the social, the political, and the cultural, in addition to the environmental and defense issues, thus assuming a valuable task of establishing an institutional bloc in South America, however, with the entry of far-right and right governments, it was observed its disarticulation, consequently of regional integration in the subcontinent, bringing new challenges.